2008
DOI: 10.1098/rspb.2008.0451
|View full text |Cite
|
Sign up to set email alerts
|

A seed predator drives the evolution of a seed dispersal mutualism

Abstract: Although antagonists are hypothesized to impede the evolution of mutualisms, they may simultaneously exert selection favouring the evolution of alternative mutualistic interactions. We found that increases in limber pine (Pinus flexilis) seed defences arising from selection exerted by a pre-dispersal seed predator (red squirrel Tamiasciurus hudsonicus) reduced the efficacy of limber pine's primary seed disperser (Clark's nutcracker Nucifraga columbiana) while enhancing seed dispersal by ground-foraging scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…In addition, we found that high phage defence correlated with weak protist defence. This suggests a trade-off in simultaneously evolving defences to phage and protist enemies [18,21,41]. Phage selection could have thus indirectly limited bacterial fitness increase to antibiotics by constraining evolution of protist defence, which correlated positively with bacterial ability to grow in the presence of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that high phage defence correlated with weak protist defence. This suggests a trade-off in simultaneously evolving defences to phage and protist enemies [18,21,41]. Phage selection could have thus indirectly limited bacterial fitness increase to antibiotics by constraining evolution of protist defence, which correlated positively with bacterial ability to grow in the presence of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, conspicuous fruit colours signal the availability of seed resources to avian seed predators in addition to mutualistic frugivores. Avian seed predators can affect the fitness of seed plants and select for particular fruit phenotypes (Siepielski and Benkman 2008). Therefore, opposing selection from birds to increase antioxidant intake as well as from seed predators might select against increased conspicuousness.…”
Section: Discussionmentioning
confidence: 99%
“…Global climate change, including warming temperatures and altered precipitation regimes, is shifting the geographic distribution of many species (Kelly and Goulden ). However, several non‐climatic factors may play a major role in determining the magnitude and direction of range shifts.…”
Section: Introductionmentioning
confidence: 99%